(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
This research was conducted to investigate organoleptical physical, and chemical quality of tempe chips that made from import and local soybean with different times fermentation. It’s used completely randomized design in factorial, American and Willis soybean be factor A (A1 and A2), and times of fermentation be factor B (B1 = 30 hours, B2 = 32 hours, and B3 = 34 hours). The observed variable were organoleptical test (performance, flavor, taste, colour and texture and chemical quality (moisture content, fat content, protein content and carbohydrat content) and phisics quality (texture) too. The result showed that interaction of both factor significantly (p< 0,01) affect the taste value in organoleptical test, moisture content, fat content, protein content and physical quality (texture) result. The best result is tempe chips that made from America soybean (A1) and 30 hours fermentation (B1).